Kinetics study of paracetamol production from para-aminophenol and acetic anhydride - Rifki Wahyu Kurnianto; Mohammad Fahrurrozi; Hilda Ismail; Raden Rara Endang Lukitaningsih; Indah Tri Nur'aini; Pudjono Lukitaningsih; Rochmadi Lukitaningsih; Ari Sudarmanto; Ratna Asmah Susidarti (Jurnal Rekayasa Proses, 2021)
In the last decade, Indonesia intensifies the efforts to reduce pharmaceutical imports. One of the initiatives is establishing a paracetamol production facility to start operating in 2024. Kinetics study is needed as a basis to design the paracetamol reactor. This study investigated the optimal temperature, reactant mole ratio, and agitation speed in the reactor for paracetamol production. In this study, aqueous solution of para-aminophenol was reacted with acetic anhydride. The mole ratio of para-aminophenol to acetic anhydride was varied to 1:1, 1:1.2, 1:1.5, and 1:2 while the temperature was varied to 80 °C, 90 °C, and 110 °C. However, due to uncontrolled heat of the reaction and limitation of the mixture’s boiling point, the actual reaction temperatures were 86 °C, 90 °C, and 108 °C. In addition, the agitation speed of 250 RPM and 350 RPM were also studied. Thin layer chromatography (TLC) and densitometry were used to determine the concentration of paracetamol in the reacting mixture. The optimum temperature, reactant mole ratio, and agitation speed in this study were 108 °C, 1:1.5, and 350 RPM, respectively. In addition, a reaction performed under those operating parameters gave the reaction rate constant of 1.95 L mol-1 min-1.